KAJIAN PENGARUH KUALITAS PRODUK, HARGA, LOKASI, DAN PROMOSI TERHADAP KEPUASAN PELANGGAN PADA GIESELIN FOOD SUKSER MAKMUR DI JEMBER - Yani Dahliani; Rohmat Hasanul Ahwal (Sekolah Tinggi Pariwisata Mataram, 2021)
The purpose of this study was to determine the effect of product quality, price, location, and promotion on customer satisfaction at Gieselin Food Sukses Makmur. This research was conducted by taking samples using the purposive sampling method, with the criteria aged 17 years, and customers of Gieselin Food Sukser Makmur. Data collection was obtained by 50 consumer data. This study uses methods such as Instrument Test, Classical Assumption Test, and Multiple Linear Regression with the help of IBM SPSS Statistic 21. The results showed by giving a questionnaire to the respondents. That product quality and location have a significant effect on customer satisfaction at Gieselin Food Sukses Makmur, while price and promotion have no significant effect on customer satisfaction at Gieselin Food Sukses Makmur.